Exploring the Moderating Effect of Multiple Role-Identities on the Relationship Between Perceived Distributive Injustice and Psychological Distress - Culatta, Elizabeth (My University, 2013)
The purpose of this research is to discover how the number and quality of role-identities affect the relationship between perceived distributive injustice and psychological distress. In order to examine the relationship between under-reward in the workplace and symptoms of psychological distress, I conduct several Ordinary Least Squared regressions using data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey to determine if a count of up to 8 roles moderates this association. Results indicate that the count of role-identities does not moderate the strong relationship between under-reward and psychological distress. However, another analysis shows that the quality of the spousal role approaches significance as a moderating effect such that a higher quality spousal role strengthens the relationship between perceived distributive injustice and psychological distress. These findings suggest that workers who do not feel fairly compensated for their job responsibilities report more symptoms of psychological distress, but the quality of another role-identity could moderate this relationship.
Keywords: Satisfaction -- Work; Employment; Health -- Mental; Health and wellbeing; Labour market; Satisfaction; Employment; Health; Work; Mental; Health and wellbeing; Employment and unemployment